Briefwechsel: 1953 - 1974 - Heidegger, Martin (Insel-Verl., 1986)
Martin Heidegger, Erhart Kästner: "Briefwechsel 1953-1974". Herausgegeben von Heinrich W. Petzet. Insel Verlag, Frankfurt am Main 1986. 152 S., geb., 38,- DM